Model Laboratorium Akuntansi Terintegrasi Untuk Perguruan Tinggi - Krisno Septyan (Jurnal Akuntansi, 2019)
This research is focused to designing of simulation accounting laboratory based on integrated computerization. This research used qualitative method descriptive, data’s got by literature review, based on experience of researcher, interviewing to user and observation to college’s needs. This laboratory will build to connect between theory and practice . Result of this designing laboratory is showing a few benefits are students know all about they will work view in industries, both situation of work and view of working place. Another output of this laboratory are increasing communication skill, working underpressure and decision making by team work or independently.